FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KOMPETENSI PETANI RUMPUT LAUT DI KABUPATEN KONAWE PROVINSI SULAWESI TENGGARA - Hartina Batoa; Amri Jahi; Djoko Susanto (Jurnal Penyuluhan, 2008)
The seaweed farmers who are competent indicated by their positive behavior on technical and management of sea weed farming. The objectives of the study are: (1) To find the sea weed farmers characteristics in relation to their competence in sea weed farming management; (2) To find evidence how they practice on sea weed farming; (3) To analyse the relationship between the sea weed farmers characteristics and their competence in sea weed farming. The study was desigred as a descriptive correlation, the data were analyzed using qualitative and quantitative methods same important results are: (1) Majority of the farmers are old age, they have enough experiences in sea weed farming, they have frequently interacted with the extension educator; (2) Most of the farmers have enough competent in: a) Selecting the seeds; b) Harvesting; c) Planting; d) Post harvest management; e) Marketing; and f) Preparation of the farming. There were high significant correlation between age, education, experiences, areal of farming, family dependent members, interaction with the extention educator, and the farmers competencies.